EFFECT OF MICRONUTRIENT FOLIAR APPLICATION ON MORPHOLOGY, YIELD AND CHEMICAL COMPOSITION OF DURUM WHEAT GENOTYPES - shiri janagard, manochehr (Journal of Agricultural Sciences (Belgrade), 2019)
Durum wheat has a comparative adaptive advantage over bread wheat under hot and dry conditions, accordingly, it feeds millions of people in the Middle East and North Africa. Under these conditions, the deficiency of nutrients, including micronutrients, is a major concern for many reasons, including calcareous soil under drought stress conditions. Therefore, growth, yield and grain quality of durum wheat under iron and zinc foliar application in a field experiment was investigated. A factorial experiment based on a randomized complete block design with three replications was conducted in Dryland Agricultural Research Institute (DARI) – Moghan. The first factor was spraying at four levels: including control and foliar spraying with iron (Fe), zinc (Zn), and iron + zinc (Fe + Zn) and the second factor was genotypes in four levels: Dehdasht (G1), Seymareh (G2), and two new genotypes (G3 and G4). Fe and Zn were sprayed at the tillering, early of heading, and milk stages, using a ratio of 2 and 1.5 per thousand (W/V), respectively. The results showed that genotypes G1, G3 and G4 produced higher grain yield per square meter than G2. This increase was due to the higher weight of 1000 grains in G3 and G4 genotypes and 1000 grain weight with higher grain number in G1. G1 and G2 had greater spike length, number of grains per spike and spikelet than G3 and G3 genotypes. In all studied traits, except for the percentage of the elements, the combination of Fe + Zn showed the highest and control had the lowest amounts. Also, application of Zn was superior to Fe. The highest Fe concentration of G1, G2, G3, and G4 was observed at Fe + Zn, control, Zn, and Fe levels, respectively. The highest zinc concentrations were observed in G3 genotype when Zn used singly or in combination. According to the results, Fe and Zn spray application due to the elimination of deficiency of these elements increases the yield of durum wheat.